Case report expanding the germline AXIN2- related phenotype to include olfactory neuroblastoma and gastric adenoma - Sarah K. Macklin- Mantia; Stephanie L. Hines; Kaisorn L. Chaichana; Angela M. Donaldson; Stephen L. Ko; Qihui Zhai; Niloy Jewel Samadder; Douglas L. Riegert-Johnson (BMC, 2020)
Abstract Background Pathogenic AXIN2 variants cause absence of permanent teeth (hypodontia), sparse hair and eye brows (ectodermal dysplasia), and gastrointestinal polyps and cancer. Inheritance is autosomal dominant with variable penetrance. Only twenty- five patients have been reported from five families. A Mayo Clinic pilot program tested 3009 newly diagnosed cancer patients for pathogenic germline variants in 83 hereditary cancer genes, including AXIN2. We found only one patient with a pathogenic AXIN2 variant. Case presentation The proband was a 49 year-old female who came to Otolaryngology clinic complaining of right-sided nasal obstruction. Biopsy of identified nasal polyp revealed olfactory neuroblastoma (esthesioneuroblastoma). Surgical resection with gross, total tumor resection was followed by radiation therapy. The patient enrolled in a clinical pilot of genetic testing and a pathogenic variant in AXIN2, c.1822del (p.Leu608Phefs*81) (NM_004655.3) was found. She was seen in Medical Genetics clinic and found to have a personal history of hypodontia. Her eyebrows, hair, and nails were all normal. She underwent upper endoscopy and colonoscopy. A four mm gastric adenoma was found and removed. Conclusions This is the first case reported on a patient with a pathogenic, germline AXIN2 variant and an olfactory neuroblastoma or a gastric adenoma. We propose that these could be features of the AXIN2 phenotype. The known association between gastric adenomas and familial adenomatous polyposis, the other Wnt/beta-catenin disorder, supports the hypothesis that pathogenic AXIN2 variants increase risk as well. As the odds of a chance co-occurrence of a pathogenic AXIN2 variant and an olfactory neuroblastoma are so rare, it is worth exploring potential causation. We are building a clinical registry to expand understanding of the AXIN2 phenotype and request any clinicians caring for patients with pathogenic AXIN2 variants to contact us.